2019
DOI: 10.1111/aas.13511
|View full text |Cite
|
Sign up to set email alerts
|

Hypervolemia does not cause degradation of the endothelial glycocalyx layer during open hysterectomy performed under sevoflurane or propofol anesthesia

Abstract: Background: Fluid-induced hypervolemia may stimulate the release of natriuretic peptides and cause degradation (shedding) of the endothelial glycocalyx layer. Sevoflurane is believed to protect the glycocalyx, but the importance of using sevoflurane to prevent shedding during routine surgery is unclear. Methods: The plasma concentrations of brain natriuretic peptide and two biomarkers of glycocalyx shedding, syndecan-1, and heparan sulfate, were measured in 26 patients randomized to receive general anesthesia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 30 publications
(76 reference statements)
1
40
0
Order By: Relevance
“…A total of 25 clinical patients scheduled for elective abdominal hysterectomy were recruited to an open label randomized parallel clinical trial with the primary aim to compare two anesthesia methods, sevoflurane and intravenous propofol, with regard to their influence the degradation of the endothelial glycocalyx layer [18]. Ethical approval (No.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 25 clinical patients scheduled for elective abdominal hysterectomy were recruited to an open label randomized parallel clinical trial with the primary aim to compare two anesthesia methods, sevoflurane and intravenous propofol, with regard to their influence the degradation of the endothelial glycocalyx layer [18]. Ethical approval (No.…”
Section: Methodsmentioning
confidence: 99%
“…After fasting overnight, patients were given general anesthesia induced with propofol but maintained with either sevoflurane as inhaled anesthetic (N = 13) or an intravenous propofol infusion (N = 12). The result of that comparison is described elsewhere [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypervolaemia has been postulated to damage the glycocalyx, at least partially by triggering the release of atrial natriuretic peptide (ANP) that caused an increase in vascular permeability and histological degradation of the glycocalyx in an animal model 19 . Findings in human patients with induced hypervolaemia (15‐25 mL/kg/h) during routine surgery are conflicting with some finding evidence of ANP release and glycocalyx shedding 20,21 while others did not 22 . However, almost all studies showed proportionate fluid retention following high volume infusions under general anaesthesia.…”
Section: Vascular Permeability and Transvascular Fluid Fluxmentioning
confidence: 99%
“…As mentioned, judicious fluid therapy and use of plasma or albumin have been proposed but require further investigation. Inhalation anaesthesia using sevoflurane has been suggested to have glycocalyx‐protecting or regenerating effects in some studies 39,40 but this was not confirmed by others 22,41 . Other drugs with possible benefits include corticosteroids, antithrombin, heparin and heparinoids 42 .…”
Section: Vascular Permeability and Transvascular Fluid Fluxmentioning
confidence: 99%